(untitled) (Journal of Nepal Geological Society, 1998)
Introduction of canal irrigation in the Kota region (western India) has significantly modified the groundwater regime of the region and has resulted in water logging and soil salinisation. Present paper focuses on diagnosis and correlation of such problems with surface irrigation in the Left Main Canal region of the Chambal command area. The results of the studies carried out for a two year period (1994- 1996) have been discussed. The area of present investigation is predominantly alluvial covered with limestone-sandstone ridges, belonging to the Vindhyan Supergroup (late Proterozoic), exposed along the western and southwestern fringe. The water table is controlled by the topography and both the pre- and post-monsoon water table profiles are quite similar. The seasonal water table fluctuation varies from 1.62 to 8.82 m. Major part of the area of study having water level depth < 6 m falls under the category of shallow water table zone. The region with <4 m depth, the ’critically water logged’ region needs special attention. The insufficient circulation of water, resulting in water stagnation at shallow depths has attributed to soil salinisation. The mitigation methods suggested in the study include judicious use of water, alternate cropping pattern, conjunctive surface and groundwater irrigation and application of subsurface drains.